The Genome Sequence of Alpine Megacarpaea delavayi Identifies Species-Specific Whole-Genome Duplication - Yang, Qiao; Bi, Hao; Yang, Wenjie; Li, Ting; Jiang, Jiebei; Zhang, Lei; Liu, Jianquan; Hu, Quanjun (Frontiers in Genetics, 2020)
Megacarpaea delavayi (Brassicaceae), a plant found the high mountains of southwest China at high altitudes (3,000–4,800 m), is used as a vegetable or medicine. Here we report a draft genome for this species. The assembly genome of M. delavayi is 883 Mb, and 61.59% of the genome is composed of repeat sequences. Annotation of the genome identified a total of 41,114 protein-coding genes. We found that M. delavayi experienced an independent whole-genome duplication (WGD), paralleling to those independent WGDs in Iberis, Biscutella and Anastatica in the early Miocene. Phylogenetic analyses based on the single-copy genes confirmed the position of the genus Megacarpaea within the expanded lineage II of the family and resolved its basal divergence to a subclade consisting of Anastatica, Iberis and Biscutella. Species-specific and fast-evolving genes in M. delavayi are mainly involved in “DNA repair” and “response to UV-B radiation”. These genetic changes may together help this species survive in high-altitude environments. The reference genome reported here provides a valuable resource for studying adaptation of this and other alpine plants to the high-altitude habitats. Running title: Genome of alpine Megacarpaea delavayi